2016
DOI: 10.1262/jrd.2015-141
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hepatic load from far-off dry period to early postpartum period on the first postpartum ovulation and accompanying subsequent fertility in dairy cows

Abstract: The aim of the present study was to investigate nutritional and metabolic parameters during the dry and early postpartum periods of ovulatory and anovulatory cows, as well as their postpartum reproductive performance. Blood samples from 20 multiparous Holstein cows were collected once a week from the far-off dry period to 3 weeks postpartum. Early postpartum (0–3 weeks) ovulation was confirmed using plasma progesterone concentration profiles, and cows were considered ovulatory if they had resumed luteal activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, despite their better metabolic status precalving, NEG cows responded to calving with a sustained increase in GGT concentrations relative to POS cows, with differences still apparent at d 28 postcalving. However, because absolute GGT concentrations were still low and within published reference intervals (Cozzi et al, 2011;Bossaert et al, 2012;Kawashima et al, 2016;Moretti et al, 2017) postcalving, we propose they do not indicate a high degree of liver stress in NEG cows. Further, this sustained increase in GGT is unlikely to be in response to hepatic processing of NEFA, as both NEFA and BHB concentrations were lower in NEG cows, leading us to conclude that it is unlikely there is liver damage.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Nevertheless, despite their better metabolic status precalving, NEG cows responded to calving with a sustained increase in GGT concentrations relative to POS cows, with differences still apparent at d 28 postcalving. However, because absolute GGT concentrations were still low and within published reference intervals (Cozzi et al, 2011;Bossaert et al, 2012;Kawashima et al, 2016;Moretti et al, 2017) postcalving, we propose they do not indicate a high degree of liver stress in NEG cows. Further, this sustained increase in GGT is unlikely to be in response to hepatic processing of NEFA, as both NEFA and BHB concentrations were lower in NEG cows, leading us to conclude that it is unlikely there is liver damage.…”
Section: Discussionmentioning
confidence: 59%
“…These cows did not differ in any other metabolite around calving, so it appears to be an acute response to the calving event. Reference intervals for GGT range from 12 to 35 IU/L (Cozzi et al, 2011;Bossaert et al, 2012;Kawashima et al, 2016;Moretti et al, 2017), so a peak of 37 IU/L is not indicative of a high level of liver damage. The NEG S-PPAI cows also had an altered hepatic activity profile, albeit in a different manner to NEG L-PPAI cows, whereby they had the greatest mean GLDH concentrations during the transition period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other blood parameters, including BUN, showed no inter‐group differences, aligning with typical values during peripartum (Kawashima, Karaki, et al., 2016; Kida, 2002; Oikawa et al., 2019). Previous studies have identified lower BCS and glucose levels and elevated AST and GGT activities in anovulatory postpartum cows (Castro et al., 2012; Kawashima et al., 2007; Kawashima, Ito, et al., 2016). Delayed uterine involution has been linked to lower total cholesterol and albumin levels and higher BUN, NEFA, and AST levels (Kawashima et al., 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have identified lower BCS and glucose levels and elevated AST and GGT activities in anovulatory postpartum cows (Castro et al, 2012;Kawashima et al, 2007;Kawashima, Ito, et al, 2016). Delayed uterine involution has been linked to lower total cholesterol and albumin levels and higher BUN, NEFA, and AST levels (Kawashima et al, 2018).…”
Section: Discussionmentioning
confidence: 99%